Anything but safe: Problems with the protection of civilians in so-called "safe zones" - David Keen (London School of Economics and Political Science (LSE), Department of International Development, 2017)
There is something rather magical in the idea of a 'safe zone' - almost as if by declaring an area to be safe one can make it so. Yet it would be more accurate to suggest that 'safe zones' are extremely fragile and depend for their existence on the complex and shifting goals of in-country actors and international actors. The history of 'safe areas' in Iraq, Bosnia, Rwanda, Sri Lanka and Sudan shows some of the severe limitations in the 'safety' that has been offered - reflecting the complex agendas of national and international actors who may perpetrate or tolerate large-scale abuse despite - and often under the cover of - an officially declared 'safe area'.
Keywords: 330; Safe zone; Safe area; Protection; Civilians; Civil war; Humanitarian space